2011
DOI: 10.1017/jfm.2011.232
|View full text |Cite
|
Sign up to set email alerts
|

Heat release rate correlation and combustion noise in premixed flames

Abstract: The sound emission from open turbulent flames is dictated by the two-point spatial correlation of the rate of change of the fluctuating heat release rate. This correlation in premixed flames can be represented well using Gaussian-type functions and unstrained laminar flame thermal thickness can be used to scale the correlation length scale, which is about a quarter of the planar laminar flame thermal thickness. This correlation and its length scale are observed to be less influenced by the fuel type or stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
54
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 53 publications
1
54
0
1
Order By: Relevance
“…The prime objectives of this study are three folds, viz., (i) to assess 62 the isotropy of the two-point spatial correlation function, Ω 1 , assumed in 63 an earlier study [6], using DNS data [21] and is about two orders of magnitude larger than other sources [24,25]. This 83 leads to a linear wave equation of the reduced form:…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The prime objectives of this study are three folds, viz., (i) to assess 62 the isotropy of the two-point spatial correlation function, Ω 1 , assumed in 63 an earlier study [6], using DNS data [21] and is about two orders of magnitude larger than other sources [24,25]. This 83 leads to a linear wave equation of the reduced form:…”
mentioning
confidence: 99%
“…Both of the values are slightly larger than the values reported in an earlier study because correlation between the far-field acoustic power and burner geometry or 16 operating flow conditions. It has been recently noted [5,6] that the two-point 17 spatial correlation of the rate of change of fluctuating heat release rate, 18 and hence the associated correlation volume v cor and its length scale, is 19 crucial to predicting combustion noise. In previous studies, different length 20 scales have been suggested to estimate v cor empirically, ranging from the 21 laminar flame thickness δ L [12], turbulence integral length scale Λ [13] to the 22 turbulent flame-brush thickness [14,15] or a combination of them.…”
mentioning
confidence: 99%
See 3 more Smart Citations